Aspectos sanitários dos abatedouros municipais do estado do Rio Grande do Norte - Moura, Edinaidy Suianny Rocha de (Universidade Federal Rural do Semi-Árido, 2011)
The object of this study was to evaluate the hygienic-sanitary conditions of the establishments and handlers of bovine meat in municipal slaughterhouses in Rio Grande do Norte. Through a check list the hygienic conditions of the establishments and handlers were observed and, according to the percentage of conformities, classified as excellent (above 80%), good (between 60 and 79,9%), regular (40 to 59,9%) and bad (below 40%). During the visits to the establishments, 210 samples were taken from the water supply, from the utensils and equipment, from the hands of the handlers, from the bovine carcasses, and from the environment, for microbiological analysis. The methodology applied on this study was based on the official parameters established by the Decree nº 30.691 (BRASIL, 1952) and by the Normative Instruction nº52 (BRASIL, 2003). The results obtained show the precariousness of the hygienic-sanitary conditions of the municipal slaughterhouses studied in Rio Grande do Norte, representing a risk to the public health of consumers in this region.
Sanitary aspects of municipal slaughterhouses in the state of Rio Grande do Norte
Keywords: Alaughterhouses; Hygiene; Meat; Microorganisms; Public health; Abatedouros; Higiene; Carne; Microrganismos; Saúde pública; CIENCIAS AGRARIAS::MEDICINA VETERINARIA